2010
DOI: 10.1021/nl103623e
|View full text |Cite
|
Sign up to set email alerts
|

Directional Roll-up of Nanomembranes Mediated by Wrinkling

Abstract: We investigate the relaxation of rectangular wrinkled thin films intrinsically containing an initial strain gradient. A preferential rolling direction, depending on wrinkle geometry and strain gradient, is theoretically predicted and experimentally verified. In contrast to typical rolled-up nanomembranes, which bend perpendicular to the longer edge of rectangular patterns, we find a regime where rolling parallel to the longer edge of the wrinkled film is favorable. A nonuniform radius of the rolled-up film is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 36 publications
(71 reference statements)
5
69
1
Order By: Relevance
“…Furthermore, the specimens are peeled along the stripe structure, which favors the wrinkling perpendicular to it. The aligned wrinkling of the metal film, with the stress being relaxed along the sensor stripe, makes it more stiff in the orthogonal direction 178 , which prevents the perpendicular stress relaxation and associated wrinkling in most regions. Instead, a slight bending across the GMR stripe could be observed on the peeled sensor elements.…”
Section: Thermally Induced Wrinklingmentioning
confidence: 99%
“…Furthermore, the specimens are peeled along the stripe structure, which favors the wrinkling perpendicular to it. The aligned wrinkling of the metal film, with the stress being relaxed along the sensor stripe, makes it more stiff in the orthogonal direction 178 , which prevents the perpendicular stress relaxation and associated wrinkling in most regions. Instead, a slight bending across the GMR stripe could be observed on the peeled sensor elements.…”
Section: Thermally Induced Wrinklingmentioning
confidence: 99%
“…159,165 Furthermore, the specimens are peeled along the stripe structure, which favors the wrinkling perpendicular to it. The aligned wrinkling of the metal film, with the stress being relaxed along the sensor stripe, makes it stiffer in the orthogonal direction, 166 which prevents the perpendicular stress relaxation and associated wrinkling in most regions. Instead, a slight bending across the entire GMR stripe could be observed on the peeled sensor elements.…”
Section: Thermally Induced Wrinkling Of Gmr Filmsmentioning
confidence: 99%
“…Li et al [20] and Schmidt [21] experimentally demonstrated the opposite scenario, namely a preference for longside rolling, in the case where bilayers are progressively etched from a substrate. They observed that when the tube circumference was much larger than the width or the aspect ratio of the rectangle was high, rolling always occurred from the long side.…”
Section: Mechanism Of Foldingmentioning
confidence: 99%
“…Control of rolling/folding direction is very important for programmed folding. For example, Schmidt demonstrated that introduction of wrinkles allows switching to short-side rolling [21].…”
Section: Mechanism Of Foldingmentioning
confidence: 99%